Silica@proton-alginate microreactors: A versatile platform for cell encapsulation - Spedalieri, Ana Cecilia (2015)
As an alternative approach to the well known Ca(II)-alginate encapsulation process within silica hydrogels, proton-driven alginate gelation was investigated in order to establish its capacity as a culture carrier, both isolated and embedded in an inorganic matrix. Control over the velocity of the proton-gelation front allows the formation of a hydrogel shell while the core remains liquid, allowing bacteria and microalgae to survive the strongly acidic encapsulation process. Once inside the inorganic host, synthesized by a sol-gel process, the capsules spontaneously redissolve without the aid of external complexing agents. The entrapped cells survive the two-step process to a significant extent; culture's growth restores the initial cell count in less than two weeks. Biosynthesis of Au nanoparticles mediated by the entrapped microalgae illustrates the preservation of the biosynthetic abilities supported by this platform.